(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article explores the types of differentiated instruction in teaching English, focusing on the differentiation of content and process. Differentiated instruction is a teaching philosophy that involves tailoring instruction to meet the diverse needs, skills, and learning styles of students. The differentiation of content involves modifying the materials, resources, and information presented to students based on their readiness levels, interests, or learning profiles. On the other hand, the differentiation of process refers to altering the way students engage with content, such as varying the methods, strategies, and activities used to support their learning. The article examines practical strategies and techniques that can be applied in the classroom to foster an inclusive learning environment where all students can succeed. It also highlights the importance of these strategies in promoting student engagement, motivation, and academic achievement in English language learning.